Strategi Kebijakan dalam Meningkatkan Kapasitas UMKM Kota Tangerang Selatan Berdasarkan Karakteristik dan Sebaran Usaha - Aries Sundoro; Siffa Annisa Fitri Ramadhani; Gusneli (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2026)
This study aims to analyze the profile and geographical distribution of MSMEs in the restaurant sector in South Tangerang City and formulate a policy strategy to strengthen business capacity based on these characteristics. Using a descriptive-qualitative approach, this study processes secondary data from the South Tangerang City Government in 2025 and interprets it through structural and spatial analysis. The results of the study show that the structure of restaurant MSMEs is dominated by micro enterprises by 83.36%, while small businesses only cover 16.64% and there are no medium enterprises. This condition indicates limited business capacity and the missing middle phenomenon that hinders the development of MSMEs towards a higher scale. In addition, the distribution of MSMEs is uneven between sub-districts, with the highest concentrations being in Pondok Aren, East Ciputat, and Pamulang, while areas such as Setu have a much smaller number of MSMEs. These findings confirm the need for targeted and contextual policies through strategies based on business structures and regional characteristics. These strategies include strengthening the basic capacity of micro businesses, facilitating small business growth, building community-based MSME clusters, and integrating structural-spatial approaches to produce more targeted policies. This research contributes to the preparation of a policy model that can support the equitable distribution of MSME growth and increase the competitiveness of the culinary sector in South Tangerang City